TORITATEJOSHI DAKE, BAKARI, DAN NOMI DALAM KALIMAT BAHASA JEPANG - Husna, Akhirul; Rini, Elizabeth; Wiyatasari, Reny (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
In writing this thesis, the writer discussed „Toritatejoshi dake, bakari, andnomi in Japanese sentences‟. The writer chose the title due to the lack of explanation of those words in Japanese books, therefore there were still many mistakes in using dake, bakari, and nomi. The first step in writing this thesis was collecting the data by the writer, analyzed the data, and presented the data descriptively.Dake, bakari, and nomi in bahasa Indonesia mean hanya and it indicates limitation. Although in Indonesian those three words can be interpreted with a same word, there are actually differences in meaning and usage of those words.Dake is a toritatejoshi which is limiting the element in a sentence that is the only element that exist and omitting another similar element. Dake can be used in many situations, such as formal and non-formal situation or in written language and verbal language. Bakari is a toritatejoshi that indicates a limitation, but with two distinctive limitating methods. First, bakari has the same meaning with dake and emphasized the element in a sentence which is the only element that exist by omitting another similar element. Bakari which has the same meaning with dake, usually can be found in a sentence containing ru verb or in a sentence with no verb on it. Second, bakari is limitating and emphasizing the element that indicates a repeated activity. Usually there is a teiru verb or activity verb. Nomi is a toritatejoshi which has the same meaning with dake. According to Professor Honda, nomi is not only used in a formal situation and in a written language, but also can be used in a verbal language, however it will gives a formal impression, this can be happened because the partner is considered as a person who has a higher degree.